Processing of Red Ginger Powder Drink to Improve the Immune System During the Covid-19 Pandemic - Hasni Yaturramadhan; Anwar Syahdat (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2021)
Introduction: Covid-19 is a disease that must be watched out for because of its relatively fast transmission and has a mortality rate that cannot be ignored and there is no definitive therapy. The body's immune system is important for maintained in this covid-19 era, in addition to consuming adequate nutrition, regular rest, supplements that contain lots of vitamin C and good sources of antioxidants for consumption. The purpose of this research is to make red ginger powder drink to improve the immune system. Methods: Experimental Research conducted at the Traditional Medicine Laboratory, Pharmacy Study Program, Undergraduate Program, Aufa Royhan University. Results: Based on the water content test that the water content in ginger powder is 1.30%. As well as the Organoleptic Test Conducted, Panelists Liked Red Ginger Powder Drink. Conclusion: Antioxidants in Red Ginger Can Boost the Immune System